Empowerment of Micro, Small, and Medium Enterprises in South Sulawesi through Participatory Economic Transformation (Case Study: Makassar City) - Hasanuddin Remmang; Hernita; Sitti Mujahida Baharuddin; Askari Hasanuddin; Arnas Hasanuddin (Journal of Public Administration and Government, 2023)
The city of Makassar is considered one of the attractive and promising cities for the development of trade in goods and services. Empowering micro, small, and medium enterprises (MSMEs) and the tourism sector in Makassar significantly influences the improvement of the economy, both at the individual and overall levels. This research aims to determine the role of small and medium-sized enterprises in grassroots economic development. In this study, the researcher focuses on variables such as labor absorption, business capital, and the level of business profit obtained by MSMEs, which are independent variables influencing community welfare. The results of this research, using the SPSS approach, have provided statistical test results indicating that all three variables positively and significantly influence community welfare (Y). These variables include labor absorption (X1) with a coefficient of b1 = 2.019, followed by business capital (X2) with a coefficient of b2 = 2.546, and the third variable, business profit (X3), with a coefficient of b3 = 3.024. In the partial test (F), the labor absorption variable (X1) is the most dominant, followed by the business capital variable (X2) and the business profit variable (X3), each influencing the level of community welfare (Y). For the partial and simultaneous tests using the SPSS system, there is an influence of these three variables on community welfare, assuming that other variables remain constant.